2003
DOI: 10.1124/dmd.31.7.833
|View full text |Cite
|
Sign up to set email alerts
|

SELECTIVITIES OF HUMAN CYTOCHROME P450 INHIBITORS TOWARD RAT P450 ISOFORMS: STUDY WITH cDNA-EXPRESSED SYSTEMS OF THE RAT

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:The aim of this study was to determine the selectivities of chemical inhibitors for human cytochrome P450 (P450) isoforms toward the corresponding rat P450 isoforms by using cDNA-expressed rat P450s (CYP1A2, CYP2A1, CYP2C6, CYP2C11, CYP2D2, CYP2E1, CYP3A1, and CYP3A2). Among the inhibitor probes for human P450s used in this study, only sulfaphenazole showed a selective inhibitory effect on the activity of the corresponding rat P450 isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 11 publications
2
71
0
1
Order By: Relevance
“…Furafylline, a 1A2 inhibitor, did not inhibit synthesis. Ketoconazole is an effective inhibitor of 1A2 in rats (Kobayashi et al, 2003) and was the only other agent that significantly inhibited demethyl-IQ synthesis at a concentration of 0.02 mM. Additional studies are needed to distinguish the specific P450(s) involved.…”
Section: Lakshmi Et Almentioning
confidence: 99%
“…Furafylline, a 1A2 inhibitor, did not inhibit synthesis. Ketoconazole is an effective inhibitor of 1A2 in rats (Kobayashi et al, 2003) and was the only other agent that significantly inhibited demethyl-IQ synthesis at a concentration of 0.02 mM. Additional studies are needed to distinguish the specific P450(s) involved.…”
Section: Lakshmi Et Almentioning
confidence: 99%
“…Although TAO is known as a potent and specific CYP3A inhibitor (Kostrubsky et al, 1997;Crincoli et al, 2008), KTZ has been reported to inhibit potently not only CYP3A1/2 activities but also CYP2C11 activity by a study using vaculovirus-infected insect cells expressing each rat P450 (Kobayashi et al, 2003). To examine whether KTZ treatment affected hepatic CYP3A and CYP2C enzyme activities in the rats, MDZ and TOL hydroxylase activities were measured in the microsomes prepared from livers collected 1.5 hours after the KTZ administration in rats administered CBZ at a dose of 400 mg/kg once daily for 4 days.…”
Section: Hepatotoxicity By Carbamazepine Requires Metabolism In Rats 963mentioning
confidence: 99%
“…These drugs also show a range of metabolic clearance values (Table 1), allowing enzymetransporter interplay to be assessed. The probes selected as markers of inhibition in the two systems were midazolam (for the CYP3A and CYP2C families) and theophylline (for the CYP1A family) (Kobayashi et al, 2003;Chovan et al, 2007). Comparison of inhibition parameters allows a cell/medium partition coefficient (Kp) to be determined that can be interpreted using previously proposed models for enzyme-transporter interplay (Liu and Pang, 2005;Shitara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%